2009
DOI: 10.1038/ajg.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Non-Variceal Upper GI Bleeding in Patients Already Hospitalized for Another Condition

Abstract: IPs are sicker than OPs. Endoscopic hemostasis and PPI therapy favorably affect rebleeding in IPs, whereas patient characteristics principally determine the threefold greater IPs mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 49 publications
12
37
0
1
Order By: Relevance
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 77%
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 77%
“…The mortality of GI complications in the postcardiac surgery patient has long been noted to be high [9]. Our findings of a 19.1% mortality confirm that this is still true today and in fact remains very elevated, even when compared to an unselected group of patients with in-hospital onset of nonvariceal UGI bleeding in the same country for whom the observed mortality rate was 11% [10].…”
Section: Discussionsupporting
confidence: 75%
“…However, in most reports, commonly reported lesions at endoscopy have included, as in our series, gastroduodenal ulcers or erosions and esophagitis [12,[20][21][22]. These findings are similar to those noted for in-hospital and outpatient patients presenting with an episode of NVUGIB [5,10]. Subsequent management therefore utilizes similar therapeutic approaches including the performance of early endoscopy, therapeutic hemostasis, and pharmacotherapy in appropriate patients [4].…”
Section: Discussionsupporting
confidence: 72%
“…Recent prospective studies have identified different predictors of mortality; it is worth noting that the use of proton pump inhibitors (PPIs) significantly reduces mortality in patients both with and without high risk stigmata of rebleeding. Moreover, the use of endoscopic treatment has been demonstrated to reduce mortality in greater proportion than drug treatment (3)(4)(5)(6). However, it has been shown that the risk factors, complications and mortality rates described in controlled trials are lower than those reported in patients who received their attention on "day-today conditions" in a tertiary care community hospital (7), which illustrates more accurately the actual conditions of medical care.…”
Section: Introductionmentioning
confidence: 76%